Analysing the Awareness Levels of Secondary School Students Regarding Tennis - Aysel KARACAOĞLU; Mehmet KARGÜN (ümit doğan üstün, 2023)
This study aimed to assess the level of awareness among secondary school students regarding tennis. The research was conducted using the survey model, which is a type of quantitative research approach. The researcher utilised a demographic information form, along with a tennis sport awareness scale that comprised of three sub-dimensions, as a means of collecting data. The research group comprises 400 students, with 41% being male and 59% being female. The normality distribution of the data was assessed to establish the appropriate statistical approaches for the investigation. Once it was shown that the data exhibited a normal distribution, the statistical techniques of T-test and ANOVA test were selected. Upon examination of the acquired findings, a notable disparity was observed in the tennis awareness of the participants in the cognitive and affective sub-dimensions based on gender, however no significant disparity was observed in the cognitive sub-dimension. The examination of the students' weekly sports practise revealed a substantial disparity in the affective sub-dimension, but no notable disparity in the cognitive and kinesthetic sub-dimensions. The research revealed a substantial disparity in the affective sub-dimension among students based on their school type. However, no significant disparities were seen in the cognitive and kinesthetic sub-dimensions. There was no discernible disparity observed in the cognitive, emotive, and kinesthetic sub-dimensions based on the students' class position. Furthermore, the research findings indicate that secondary school pupils generally possess a low degree of cognitive and psychomotor skills awareness regarding tennis activity, but their affectivity level is somewhat developed.